A educação ambiental na educação do campo, das águas e da floresta: etnografia de uma escola rural manauara - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The socio-environmental concept is based on a complex and interdisciplinary rationality. It thinks of nature not as an untouchable environment, but as a space of socio-biocultural interactions in constant transformation, whose perspective considers the human presence as a subject that belongs to the web of relationships of social, natural and cultural life and interacts with it. In this sense, for the socio-environmental view, the changes resulting from interactions between human beings and nature are not always harmful, they are often sustainable, increasing biodiversity through the actions taken (CARVALHO, 2011). Thus, in this research, we seek to understand the contribution of environmental education to the formation of socio-environmental citizenship of children in early childhood education and elementary school students at an agrarian reform settlement school in rural Manaus. To respond to this central objective, some specific objectives were used, namely: i) to explain the trajectories of struggles of family farmers and their ways of life; ii) to understand how environmental education practices contribute to the construction of students’ peasant identity; iii) to understand how environmental education work impacts students on environmental issues; iv) and describe environmental thematics developed at different school levels. The research was carried out in a municipal school that serves children in early childhood education and students from the 1st to 9th years of elementary school. Based on a qualitative approach, ethnographic in nature, with data collection carried out in five simultaneous stages (participant observation, interview, documentary, questionnaire and drawing technique). The results showed that teachers work on environmental issues, directing their practices to the students' rural context, contributing to the formation of socio-environmental citizens committed to valuing life in all its forms, whose practices are intentional, so that students perceive the connections between their individual and collective actions that cause positive or negative local, regional and global environmental impacts, in order to exercise their citizenship and occupy spaces of social participation with a view to transforming their reality and contributing to the transformation of the reality of other citizens, in search for a fairer life for all (CECCON, 2013; PORTO, 2003).
Keywords: Educação Ambiental - Amazônia; Agricultura Familiar - Amazônia; OUTROS: CIÊNCIAS AMBIENTAIS; Educação Ambiental; Educação Ambiental na Amazônia; Educação; Reforma Agrária; Agricultura Familiar